Special issue on process systems engineering - Hussain, Mohd Azlan; Aroua, Mohamed Kheireddine (Wiley, 2007)
Process Systems Engineering is broadly defined as an academic and technological field related to methodologies for chemical engineering systems. These methodologies include steps of planning, design, operation, and control of various operations in chemical process systems. However, the context of Process Systems Engineering has been expanded from the design of unit operations to the design of chemical processes and large process systems. It has also evolved from design problems to include operational problems, and from singleobjective optimization to multi-objective optimization. These advances have been made possible in a short period of time due to the rapid development of computer technology today. The papers of this special edition have been compiled to demonstrate the changes and advances that have been made in the field of Process Systems Engineering in various aspects involving Chemical Engineering and its related processes. It also reflects some of the important issues facing process engineers within this Asia-Pacific region at large.